2009
DOI: 10.1177/110330880801700102
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of youth citizenships in the European Union

Abstract: The aim of this article is to demonstrate the diversity of youth civic action by pre-senting several examples of what young citizenship concretely is and can be in the European Union (EU). This will be done by placing Theodore Marshall's (1950) classical, modern formulation of citizenship in different contemporary contexts, and thus also going beyond the modern conception of citizenship. Contexts such as the globalizing world, new conditions for transitions into adulthoods, new forms of political participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
(2 reference statements)
1
11
0
Order By: Relevance
“…The literature in the field (Sloam, 2013;Hoikkala, 2009;Barber, 2010;Gaiser et al 2010) reveals that young people tend to opt more often than the rest of the population for alternative forms of political participation such as: joining protest movements, signing petitions online or expressing points of view on public matters on social networks and online forums or joining local associations and nongovernmental organisations. These new forms of political participation give young people the chance to voice their opinions by means of informal, noninstitutional methods (Harris et al, 2010;Sloam, 2013) which are considered to have a more direct influence on political decisions (Dalton, 2008).…”
Section: New Forms Of Political Participationmentioning
confidence: 99%
“…The literature in the field (Sloam, 2013;Hoikkala, 2009;Barber, 2010;Gaiser et al 2010) reveals that young people tend to opt more often than the rest of the population for alternative forms of political participation such as: joining protest movements, signing petitions online or expressing points of view on public matters on social networks and online forums or joining local associations and nongovernmental organisations. These new forms of political participation give young people the chance to voice their opinions by means of informal, noninstitutional methods (Harris et al, 2010;Sloam, 2013) which are considered to have a more direct influence on political decisions (Dalton, 2008).…”
Section: New Forms Of Political Participationmentioning
confidence: 99%
“…Helve, therefore, claims that it is worth asking what type of citizenship will be suitable for young people with floating values and a variety of subcultures [17]. Hoikkala [18] describes the young people of today who are around thirty years old as the "sandwich generation" (p. 10). The "sandwich generation" extend their youth by travelling, consuming and enjoying themselves.…”
Section: Youth Participation In Formal Democracymentioning
confidence: 99%
“…However they get anxious, have feelings of loneliness and suffer from psychophysical symptoms. He also talks about the "yo-yo" generation that is constantly drifting between work and unemployment [18]. Investigations in Sweden and other countries have shown that young people are concerned about society and want to influence questions that are important for them Sörbom [19], Sörbom [20], Sörbom [21] and Harris et al, [1].…”
Section: Youth Participation In Formal Democracymentioning
confidence: 99%
“…As the transversal or softs skills such as adaptability, versatility, flexibility and creativity are increasingly valued and required in modern labour markets, to succeed requires acquire more individualised skills, communication skills and social capital [49,50]. Moreover, as a result of individualization, demands are put on young people to not to blame failure on structural conditions but to see this as a result of their own "underdeveloped entrepreneurial spirit" [51].…”
Section: Volunteering As An Opportunity For Skills Development and Cumentioning
confidence: 99%